Asymmetric Information about Migrant Earnings and Remittance Flows - Seshan, Ganesh; Zubrickas, Robertas (World Bank, Washington, DC, 2015)
This paper examine asymmetric information about migrant earnings and its implications for remittance behavior using a sample of Indian households with husbands working overseas in Qatar. On average, wives underreport their husbands’ income and underreporting is more prevalent in households with higher earning migrants. The discrepancy in earning reports is strongly correlated with variation in remittances: greater underreporting by wives is associated with lower remittances. An exchange model of remittances is developed with asymmetric information and costly state verification. The optimal remittance contract prescribes a threshold for remittances that invites verification only if unmet. The model’s predictions closely match our empirical findings.